Selective Growth of High‐Density Anatase 101 Twin Boundaries on High‐Energy 001 Facets. Issue 3 (27th September 2020) - Lu, Yang; Liu, Xiaolu; Liu, Hongwei; Wang, Yun; Liu, Porun; Zhu, Xiaoguang; Zhang, Yunxia; Zhang, Haimin; Wang, Guozhong; Lin, Yue; Diao, Hui; Zhao, Huijun
Abstract : Crystal lattices with abundant twinning boundaries are rendered with unique electrical, optical, chemical, and mechanical characteristics; however, it is highly challenging to controllably fabricate such material structures in a facile and high‐throughput manner. Herein, a facile feeding‐triggered growth approach to selectively grow high‐density anatase TiO2 101 twin boundaries (TBs) on the 001 faceted high‐energy surfaces of anatase TiO2 single crystals is reported. The growth of the TB rich structures is found to be highly sensitive to the amount of feeding TiN and HF concentrations. The resultant anatase 101 twinned structures are systematically characterized and analyzed. When compared with the twin structure‐free anatase TiO2 single crystals, the obtained anatase TiO2 single crystals with the densely populated 101 TBs on the 001 faceted surfaces exhibit a significantly enhanced activity toward the photoelectrocatalytic oxidation of water and organic compounds. The demonstrated twin structure growth approach herein is adaptable to grow rich twin structures on other crystals for diversified applications. Abstract : Differing from the commonly observed anatase 112 twin, a high‐density anatase 101 twinned nanosheet overlayer is selectively grown on the 001 faceted anatase TiO2 surfaces via a feeding‐triggered hydrothermal approach. The twinned nanosheets consist of rich anatase 101 twin boundaries and possess superior photoelectrocatalytic activities toward the oxidation of water and organic compounds.